Changing schools: A study of primary secondary transfer using Vygotsky and Bernstein - Daniels, H; Tse, H; Ortega, L; Stables, A; Cox, S (Taylor and Francis, 2019)
This article is concerned with the influences that are brought to bear on the design of school buildings and the effects that the design of these buildings have on those who teach and learn in them. The article also focuses on the ways in which design is altered in and through the practices of these occupants. We argue that there is a mutual shaping of design and practice in these schools. We deploy the theory of socio-genesis developed by Lev S. Vygotsky and the sociology of pedagogy developed by Basil Bernstein in order to study the consequences for students of different trajectories of transfer between different designs and pedagogic cultures of primary and secondary schools in England. Our intention is to contribute to current debates about the effects of new school designs and the enduring concerns raised by difficulties that some students encounter in transitions between schools.